Synthesis and characterization of undopped bismuth ferrite oxide nanoparticles for the application of cancer treatment. (2021) - Rameshkumar, C.; Gayathri, R.; Subalakshmi, R.
Abstract: The Bismuth Ferrite nanoparticles (BiFeO3 ) is synthesized by the sol–gel method using Bismuth nitrate [Bi (NO3 )3 ·H2 O] and Iron nitrate [Fe (NO3 )3 ·9H2 O] as a base material, which is applied for the cancer treatment. Multiferroic materials are of particular interest due to the co-existence of ferromagnetic and ferroelectric properties. Among various multiferroics, bismuth ferrite (BiFeO3 or BFO) is the only material that shows both ferroelectric and antiferromagnetic properties at room temperature. In this work, bismuth iron oxide nanoparticles are synthesized using sol–gel technique. The prepared samples were characterized by X-ray diffraction of powder (XRD), Scanning Electron Microscope (SEM), Energy Dispersive Spectroscopy (EDAX) and antimicrobial activity studies. The surface morphology studies confirm the growth of bismuth ferrite nanoparticles with their diameters in the range of 55 nm to 150 nm (Submicron range). The XRD analysis concludes the rhombocentered structure of synthesized nanoparticles. Topographical studies by SEM micrograph showed high level of agglomeration tendency in the sample and EDAX studies confirmed the elemental compositions in the sample. As the result of antimicrobial studies, these nonmaterials are highly impressive in cancer treatment.